Review of the genus Neotetricodes Zhang et Chen (Hemiptera: Fulgoromorpha: Issidae) with description of two new species - Chang, Zhi-Min; Yang, Lin; Zhang, Zheng-Guang; Chen, Xiang-Sheng (Zootaxa, 2015)
Two new species of the issid genus Neotetricodes Zhang et Chen (Hemiptera: Fulgoromorpha: Issidae): Neotetricodes longispinus Chang et Chen sp. nov. (China: Yunnan) and Neotetricodes xiphoideus Chang et Chen sp. nov. (China: Yunnan) are described and illustrated. The generic characteristic is redefined. A checklist and key to the species of the genus are provided. The female genitalia of the genus are firstly described.